(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This comprehensive clinical anatomy article scrutinizes the intricate structures on the side of the face, with a particular focus on the preauricular masticatory area, post-mandibular fossa, preauricular salivary gland, facial nerve, and temporomandibular joint (TMJ). Through meticulous examination, the study aims to unravel the spatial relationships, anatomical features, and clinical significance of these structures. This in-depth exploration provides valuable insights for medical professionals, surgeons, and anatomists, enhancing their understanding of facial anatomy and its applications in clinical practice